Visualizing geometry: exploring the role of geogebra-assisted 6E-IM model in enhancing students’ spatial abilities - Prasetya, Natan; Gorky Sembiring, Maximus; Sudirman, Sudirman; Rodríguez-Nieto, Camilo Andrés (International Journal of Mathematics and Sciences Education, 2025)
Students’ spatial visualization ability is a key component in understanding geometry, yet many students exhibit suboptimal performance in this area. This study aimed to (1) evaluate the quality of the Geogebra-assisted 6E-IM learning model, (2) examine its effect on students' spatial visualization ability, and (3) describe students' ability levels after receiving the intervention. A sequential explanatory mixed-methods design was used. The independent variable was the Geogebra-assisted 6E-IM model, while the dependent variable was students’ spatial visualization ability. A total of 60 students participated, with 30 assigned to the experimental group and 30 to the control group. Data were collected through tests, interviews, and questionnaires. Quantitative results showed that students in the experimental group significantly outperformed the control group (p < 0.05), indicating a positive effect of the Geogebra-assisted 6E-IM model on spatial visualization ability. Qualitative analysis revealed that students with high ability met all spatial visualization indicators; those with moderate ability met two indicators, while those with low ability met only one. These findings demonstrate that the integration of Geogebra in the 6E-IM learning model can effectively enhance students’ spatial visualization skills in geometry. This study contributes to the development of innovative, technology-integrated instructional strategies in mathematics education.